Comparative analysis of the perception of nuclear risk in two populations (expert/non-expert) in France - Sandra Perez (Energy Reports, 2020)
In an effort to reduce CO2emissions, many countries throughout the world are initiating plans to transition to more sustainable forms of energy. Nuclear energy would appear to be a powerful contender to replace fossil fuels, or at least be an unavoidable option, from an energy-mix perspective. However, nuclear energy suffers from a poor image among certain populations, especially the young, who favor the development of renewable energies. We wanted to get a more accurate read of what was happening in France, one of the most nuclearized countries in the world, where the share of nuclear energy is greater than 70%. Since plans are underway to reduce this level to 50% by 2035, understanding popular perceptions on this matter is even more important. In order to gain a better understanding, we interviewed an “expert” population and compared the results obtained with a so-called young “non-expert” student population. The first group is composed of firefighters, about half of whom have attended training in radiological risks, and the other, a non-expert population, composed of students from Université Côte d’Azur (UCA), who are potentially influenced (for better or worse) by social media. The aim of this study is to compare and contrast any differences in perception that these two distinct populations may have on the subject of nuclear energy.